Management Principles of Collaboration-Based Classroom Settings in Interactive Learning - Pangat Ketug Priyono; Anggi Budi Hartarto; Nurfuadi Nurfuadi (EDUJAVARE: International Journal of Educational Research, 2026)
The 21st-century learning paradigm demands a shift from a teacher-centered model to a student-centered one, emphasizing collaboration and interactivity. However, this pedagogical transformation is often not accompanied by a restructuring of the physical classroom environment. Rigid and static classroom settings actually become a major obstacle to the creation of collaborative dynamics. This article aims to examine and formulate the principles of classroom settings based on collaboration and interactive learning. This research uses a library study method with a descriptive-analytical approach. Data sources are obtained from literature related to learning environment design, collaborative pedagogy, and environmental psychology. The study results formulate six main principles, namely: Spatial Flexibility, Visibility and Accessibility, Availability of Flexible Learning Zones, Technology Integration, Support for Student Autonomy, and Stimulating Aesthetics. The application of these principles has been theoretically proven to increase active participation, facilitate group work, and create a sense of ownership and psychological comfort for students. In conclusion, the classroom setting is not merely a decorative element, but a strategic pedagogical component that must be consciously designed to realize the goals of interactive and collaborative learning.